Determination of Total Boron in fertilizers by flame atomic emission spectrometry - Sánchez G., Eddy Rey (2003)
An alternative analytlcal method to the spectrophotometric method AOAC 982.01 has been developed to determine total boron in organic liquid fer1ilizers using emission spectrometry with nitrous oxide-acetylene flame in a wavelength of 249,7 nm. The method could apply to boron concentrations 0f 1,0 - 2,0 % w/w. The results showed 1% deviation to the official method.